Evaluation of sensitivity of TaqMan RT-PCR for rubella virus detection in clinical specimens - Okamoto, Kiyoko; Mori, Yoshio; Komagome, Rika; Nagano, Hideki; Miyoshi, Masahiro; Okano, Motohiko; Aoki, Yoko; Ogura, Atsushi; Hotta, Chiemi; Ogawa, Tomoko; Saikusa, Miwako; Kodama, Hiroe; et al. (Journal of clinical virology, 2016)
•We evaluated a TaqMan RT-PCR assay for the rubella surveillance system in Japan.•We tested its sensitivity with all rubella virus genotypes and clinical specimens.•Detection limits for the rubella virus genotypes ranged from 1 to 10 pfu/reaction.•The sensitivity of the TaqMan RT-PCR was lower than the conventional nested RT-PCR.•The assay is appropriate for throat swab and urine samples until 5days of illness. An easy and reliable assay for detection of the rubella virus is required to strengthen rubella surveillance. Although a TaqMan RT-PCR assay for detection of the rubella virus has been established in Japan, its utility for diagnostic purposes has not been tested. To allow introduction of the TaqMan RT-PCR into the rubella surveillance system in Japan, the sensitivity of the assay was determined using representative strains for all genotypes and clinical specimens. The detection limits of the method for individual genotypes were examined using viral RNA extracted from 13 representative strains. The assay was also tested at 10 prefectural laboratories in Japan, designated as local reference laboratories for measles and rubella, to allow nationwide application of the assay. The detection limits and amplification efficiencies of the assay were similar among all the representative strains of the 13 genotypes. The TaqMan RT-PCR could detect approximately 90% of throat swab and urine samples taken up to 5days of illness. These samples were determined positive by a highly sensitive nested RT-PCR. The TaqMan RT-PCR could detect at least 10 pfu of rubella virus. Although the sensitivity was somewhat lower than that of the conventional nested RT-PCR, the TaqMan RT-PCR could be more practical to routine tests for rubella laboratory diagnosis and detection in view of the rapid response and reducing risks of contamination.